Driving cars to the clinic for solid tumors. Issue 3 (June 2018) - Castellarin, Mauro; Watanabe, Keisuke; June, Carl; Kloss, Christopher; Posey, Avery
Abstract FDA approval of chimeric antigen receptor T cells (CART cells) is the culmination of several decades of technology development and interrogation of the properties of these gene therapies. CART cells exist as personalized "living drugs" and have demonstrated astounding anti-tumor efficacy in patients with leukemia and lymphoma. However, the future promise of CART efficacy for solid tumors, the greatest unmet burden, is met with a number of challenges that must be surmounted for effective immune responses. In this review, we discuss the next-generation developments of CARs to target solid tumors, including fine-tuned and combinational-targeting receptors. We consider the structural intricacies of the CAR molecules that influence optimal signaling and CART survival, and review pre-clinical cell-intrinsic and cell-extrinsic combinational therapy approaches.